Novel Techniques for Increasing Seed Potato Productivity - Sadawarti, Murlidhar J.; Singh, S. P.; Buckseth, Tanuja; Kumar, Vinod; Singh, Rajesh K.; Katare, Subhash; Sharma, Ashwani K.; Jatav, Pooja; Deora, Deepanshi; Khambalkar, Priyadarshani; et al. (Chronicle of Bioresource Management, 2024)
Challenge before government seed producing agencies all over the world is providing high quality seed of potato at affordable price at right time. Currently largely seed potato is being produced by conventional system of seed potato production which has few bottlenecks like, low multiplication rate (1:6), high seed (tuber) rate, dynamic amassing of degenerative infections, perishability, massiveness and slower process of generating 100% healthy seed stock. Rapid multiplication techniques like aeroponic system of seed production has well integrated all over the world in seed production programme due to high seed multiplication rates (1: 20-80). New techniques like apical root cutting (ARC) and sprout cutting has the potential for large scale multiplication as they are rapid, cost effective and farmer’s friendly. As ARC and sprout cuttings are promising technologies and their technical advancements have been or are being examined so that it can be integration in seed potato production system.